Design and characterization of a novel single-particle polar nephelometer. Issue 4 (2nd April 2016) - Nakagawa, Maho; Nakayama, Tomoki; Sasago, Hiroshi; Ueda, Sayako; Venables, Dean S.; Matsumi, Yutaka
ABSTRACT: A new polar nephelometer (PN) has been developed to measure simultaneously the scattering angular distributions from 11.7° to 168.3° for individual particles in planes parallel and perpendicular to the polarization of the incident laser beam. Each detection plane had 21 silicon photodiode detectors to detect scattered light at a rate of 100 Hz. Laboratory experiments to validate the performance of the instrument were conducted using nearly mono-disperse spherical particles (polystyrene latex [PSL] and nigrosine) and nonspherical particles (sodium chloride [NaCl] and soot). The observed scattering angular distributions for individual PSL particles were in good agreement with the results of simulations based on Mie theory. Complex refractive index values for nigrosine particles were determined by comparing the observed scattering angular distributions with the results of simulations. Clear differences between the measured scattering angular distributions and the results of simulations based on Mie theory assuming spherical particles were observed for NaCl particles (mobility diameters of 500 and 700 nm) and propane soot particles (mobility diameters of 300, 500, and 700 nm). These results are reasonably explained by theoretical predictions. We also conducted initial observations of ambient particles in Nagoya city, Japan. Scattering angular distributions for particles with a mobility diameter of 500 nm and an average effective density of 1.4 or 0.3 g/cm 3, which were selected with a combination of differential mobility analyzer and aerosol mass particle analyzer, were measured using the PN. As results, scattering angular distributions for nearly spherical inorganic and organic particles with an average effective density of around 1.4 g/cm 3 were found to be distinguishable from nonspherical particles with an average effective density of around 0.3 g/cm 3 . This study has demonstrated that our PN has the potential to distinguish between spherical and nonspherical particles. Copyright © 2016 American Association for Aerosol Research